Thermoelectric properties of synthesized Mg2Si0.95-xGe0.05Sbx by spark plasma sintering. Issue 1735 (2015) - Sasaki, Asumi; Arai, Koya; Kimori, Yuto; Nakamura, Tomoyuki; Fujimoto, Kenjiro; Yamaguchi, Yuki; Tamura, Ryuji; Iida, Tsutomu; Nishio, Keishi
Abstract: Magnesium silicide (Mg2 Si) has attracted much interest as an n -type thermoelectric material because it is eco-friendly, non-toxic, light, and relatively abundant compared with other thermoelectric materials. In this study, we tried to improve the thermoelectric performance by doping Sb and Ge in the Mg2 Si, as well as further optimizing x in the carrier concentration to cause phonon scattering. A high purity Mg2 Si was synthesized from metal Mg and Sb doped Si-Ge alloy by using spark plasma sintering (SPS) equipment. The sintered samples were cut and polished. They were evaluated by using X-ray diffraction (XRD) and X-ray fluorescence (XRF) analyses. The carrier concentration of the samples was measured by using Hall measurement equipment. The electrical conductivity and Seebeck coefficient were measured by using a standard four-probe method in a He atmosphere. The thermal conductivity was measured by using a laser-flash system. We succeeded in obtaining a Sb doped Mg2 Si0.95 Ge0.05 sintered body easily without any impurities with the SPS equipment. The electrical conductivity of the sample was increased, and thermal conductivity was decreased by increasing the amount of doped Sb. The dimensionless figure of merit ZT became 0.74 at 733 K in the Mg2 Si0.95- x Ge0.05 Sb x sample with x = 0.0022.